2021
DOI: 10.1021/jacs.1c05268
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field-Induced Chirality in Columnar Liquid Crystals

Abstract: We describe a novel class of tetraphenylbenzene-based discotic molecules with exceptional self-assembling properties. Absorption and fluorescence studies confirmed the formation of Jtype aggregates in solution. The discotic mesogens also show an enhancement of the emission upon aggregation. Interestingly, these discotic molecules displayed enantiotropic hexagonal columnar liquid crystal (LC) phases that can be switched into a helical columnar organization by application of an electric field. The helical column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The polar chains are along the polymer axis and can be polarized and switched by application of electric f ields. • Xu, B.; Swager, T. M. Rigid Bowlic Liquid Crystals Based on Tungsten-Oxo Calix [4]arenes: Host-Guest Effects and Head-to-Tail Organization J. Am.…”
Section: ■ Key Referencesmentioning
confidence: 99%
See 3 more Smart Citations
“…The polar chains are along the polymer axis and can be polarized and switched by application of electric f ields. • Xu, B.; Swager, T. M. Rigid Bowlic Liquid Crystals Based on Tungsten-Oxo Calix [4]arenes: Host-Guest Effects and Head-to-Tail Organization J. Am.…”
Section: ■ Key Referencesmentioning
confidence: 99%
“…2021, 143, 9260−9266. 4 Building on our propeller concepts, we found that materials could be made that were too dynamic to resolve spontaneously. However, by applying electric f ields along the column axes we induce chirality in the conformations of the aromatic mesogenic cores.…”
Section: ■ Key Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly used chiral inducers are helical self-assembly scaffolds, cholesteric liquid crystal compounds, and chiral biomolecules (especially, amino acids, peptides, and DNA), and these can be used to synthesize different kinds of chiral nanostructures. , The other strategy is the photon-to-matter chirality transfer. This method fabricates chiral nanomaterials that possess specific optical or magnetic properties by applying external driving forces, such as an electric field, magnetic field, or circularly polarized (CP) light. Compared to the traditional chemistry-driven chirality transfer, utilizing the physical light–matter interaction properties of plasmonic material has opened up a novel opportunity for synthesizing chiral nanostructures by CP light. This is becoming a promising research direction due to the dependence on the transfer of spin angular momenta .…”
Section: Introductionmentioning
confidence: 99%